Somaclonal Variation in Chrysanthemum × morifolium Protoplast Regenerants - Eeckhaut, Tom; Van Houtven, Wouter; Bruznican, Silvia; Leus, Leen; Van Huylenbroeck, Johan (Frontiers in Plant Science, 2020)
Chrysanthemum x morifolium protoplasts were isolated and regenerated to assess possible protoclonal variation in the regenerants. After a preliminary screening of the potential of different regeneration systems for protoplast regeneration, we produced a series of cut chrysanthemum ‘Arjuna’ leaf protoplast regenerants through liquid culture. Regenerants (54) were vegetatively propagated and grown under a commercial production system in 2 different seasons. All screened regenerants were significantly affected with regard to either flower number, flower size, flower weight, leaf weight, stalk weight, or plant size. A significant plant size reduction in 43/52 and 48/49 regenerants for both seasons was the most recorded effect. Also a reduction in flowering induction time up to 10 days, altered flower types and colors were observed. Differences between growing seasons were notable. Possible molecular backgrounds including genome size variation and commercial applications in breeding of chrysanthemum are discussed.